Narrating Experiences of Breast Cancer: Reflections of Women Attending a Private Hospital in Bloemfontein, South Africa - Heggenstaller, Alessandra K.; de Wet, Katinka; Coetzee, Jan K.; Elliker, Florian (Qualitative Sociology Review, 2017)
It is commonly thought that breast cancer, like many other cancers, is an illness equivalent to a death sentence. Though this may be true in some cases, the majority of women diagnosed with breast cancer do survive this illness. Breast cancer is a growing illness and is continuing to affect women worldwide, including developing countries like South Africa. Furthermore, this country’s medical system operates in terms of a duality. Here, hospitals and healthcare are mainly situated in either state operated institutions or in privately run practices. This duality emphasizes the inequality within the socio-economic classes, treatment regimens, and ethic-of-care. This article deals with how women from the higher socio-economic stratum of the deeply polarized South Africa deal with breast cancer. The aim is to understand how each participant renegotiates and transforms her self-perception, her identity, and issues around femininity. In addition, the authors also seek to understand if this medical encounter influences the participants’ sense of embodiment, as well as how the medical encounter impacts on their everyday lifeworld.